Effects of cumulative sleep restriction on self‐perceptions while multitasking. (22nd November 2012) - Sallinen, Mikael; Onninen, Jussi; Tirkkonen, Katriina; Haavisto, Marja‐Leena; Härmä, Mikko; Kubo, Tomohide; Mutanen, Pertti; Virkkala, Jussi; Tolvanen, Asko; Porkka‐Heiskanen, Tarja
Summary This study addressed a rarely studied question of self‐perceptions of performance and overall functional state during cumulative sleep restriction and the ensuing recovery period. Twenty healthy male volunteers, aged 19–29 years, were divided into a sleep restriction group (n = 13) and a control group (n = 7). On the first 2 nights, the sleep restriction group had an 8‐h sleep opportunity that was restricted to 4 h for the next 5 nights, and then restored to 8 h for the last 2 nights. The control group had an 8‐h sleep opportunity each night. Each day participants accomplished 50‐min multitask sessions and gave self‐ratings in their connection. Similar to our previous findings on multitasking performance, self‐perceived task performance, sleepiness and mental fatigue impaired during the sleep restriction and returned to baseline during the recovery phase. Self‐perceived mental effort, tension, task difficulty and task pace showed no sensitivity to the sleep restriction. We concluded that sleep‐restricted individuals can probably make use of some self‐perceptions when assessing their 'fitness for duty'. However, at the individual level these measures seem to be inaccurate in revealing actual performance impairments.